Optimization of steam turbine extraction pressures - Egelio?lu, Fuat; Aybar, Hikmet Ş. (American Society of Mechanical Engineers, 2003)
A power plant has to be simulated to perform parametric study, to make optimization, to set operation characteristics, etc. There are many methodologies for modeling and simulation of power plants. In this study, a very simple yet detailed power plant simulation has been developed by Vis-Sim that is visual block oriented visualization package. An iterative method (or algorithm) has been developed to obtain the optimum extraction pressures. As an application of the simulator and optimization algorithm, a 60-MWe oil-fired power plant, which is a local power plant, has been simulated. The results of the simulator are in good agreement with the actual plant data without optimization, and the optimized extraction pressures for this power plant have been obtained.
2003 International Joint Power Generation Conference --
Keywords: Algorithms; Computer simulation; Energy efficiency; Enthalpy; Extraction; Feedwater heaters; Friction; Iterative methods; Optimization; Pressure effects; Steam power plants; Power plant simulators; Thermal efficiency; Steam turbines